Male contact can replace equine chorionic gonadotropin(eCG) injection in anestrus progesterone-treated dairy goats - Álvarez Ramírez, Lorenzo; Gamboa Beltrán, Débora (Spei Domus, 2024)
Introduction: Equine chorionic gonadotropin (eCG) is a crucial component of progestogen treatments to induce reproductive activity in goats. However, its repeated use leads to antibody production, and its origin raises animal welfare concerns. Methodology: This study compared the reproductive performance of anestrus dairy goats treated with eCG or exposed to males following a 14-day progesterone treatment. Seventy-one anestrus goats were implanted with a controlled internal drug release (CIDR®) device and placed in one of three groups: the eCG group (n = 23) received an injection of 200 IU of eCG, the male group (M, n = 24) was exposed to a male in the same pen for a period of seven days, and the control group (C, n = 24) received no additional treatment. Results: Estrus, ovulation, and pregnancy rates were recorded. Estrus rates and the interval to estrus (h±SE) in the eCG (95.7% and 36.4±2.8, respectively) and M groups (95.9%, 48.2 ± 2.7) were significantly different from those in the control group (58.3%, 62.7 ± 3.6; p
Keywords: Biostimulation; Estrus induction; Social stimulation; sexual stimulation